Effect of resistance training on structural injuries of skeletal muscle induced by different doses of Boldenone in male rats - Maliheh Ardakanizadeh; Soroush Saeedpour; Sayed Javad Ziaolhagh (مجله دانشگاه علوم پزشکی بیرجند, 2022)
Background and Aims: The use of anabolic steroids is common among athletes who perform resistance training; nonetheless, the effect of their abuse, along with resistance training, on the structural destruction of skeletal muscles is not fully understood. The present study aimed to assess the effect of different doses of Boldenone, along with resistance training, on muscle injury. Materials and Methods: In this experimental study, 36 male Wistar rats (189.53±5.94 gr) were randomly assigned to six groups (n=6 in each group): control, Boldenone (2mg/kg), Boldenone (5mg/kg), training, training+Boldenone (2mg/kg), and training+Boldenone (5mg/kg). Boldenone steroid was injected twice a week into the rat serine muscle. The resistance training program consisted of ladder-climbing 5×3, three times per week for six weeks. It began with 50% of the one-repetition maximum of rats and increased to 100% in the final week. Histopathological changes in quadriceps muscle tissue were assessed using hematoxylin staining and optical microscopic. To assess the normality of data, the Kolmogorov-Smirnov test was used. One-way analysis of variance (ANOVA) and Tukey post hoc test were employed for data analysis at a significance level of P≤0.05. Results: Based on the results, there was no significant difference in the weight ​​of rats in all groups. In the groups receiving Boldenone, mild and moderate damages were observed in the tissue structure of the quadriceps muscle, which was slightly improved by performing resistance exercises; however, the difference was not statistically significant (P<0.05). Conclusion: Resistance training in the present study did not seemingly prevent or improve the muscle injuries caused by taking Boldenone steroids.